EFFECT OF IMPACT ANGLE AND PARTIKEL SIZE ON THE EROSION CORROSION OF LOW CARBON STEEL - SYAHID (NIM : 23107017);Pembimbing : Dr. Ir. Bambang Widyanto, MUHAMMAD
The aim of research was to observe the effect of impact angle and the particle size on erosion-corrosion of low carbon steel with varios consentrations of NaCl. The liquid jet impingement is used in this research. Experiments are done at the impact velocities of 4.42 m/s for 4 hour with material specimens St 37. The surface of specimens was observed by macro camera and microscope stereo. Cross section observed by microscope optic. The surface contour was measured by dial gauge. The distribution of wall shear stress simulated by computational Fluid Dynamics (CFD). The results showed that the impact angle 45 o produce weight loss are higher than angle at 30 o and at 90 o with the same others parameter. The results also show that positive synergism between corrosion and erosion.